Taxation, Accountability, and Cash Transfers : Breaking the Resource Curse - Devarajan, Shantayanan; Do, Quy-Toan (World Bank, Washington, DC, 2021)
Why is governance in resource-rich countries so poor This paper argues that it is because governments in these countries do not rely on taxation, which is an important instrument for citizens to hold their governments accountable. Using a game-theoretic model, the authors show that the combination of low taxes and weak governance can be an equilibrium in an economy with sizeable mineral revenues. As income from natural resources ultimately declines, replacing it with tax revenues may require governments to give control of these proceeds to citizens, in the form of cash transfers say, as a credible commitment to accountability, thereby breaking the country out of its resource curse.